2000
DOI: 10.1002/1521-396x(200011)182:1<347::aid-pssa347>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Luminescence of Porous Si and InP

Abstract: The kinetics of porous Si and InP luminescence has been investigated using short (10 ps, 2 ns and 14 ns) laser pulses for excitation, by a streak camera with 10 ps time-resolution and photomultiplier for measuring fast and slow increase and decay of the intensity of luminescence. Two luminescence bands with fast and slow decay have been registered within the usually observed single wide band in the time-resolved photoluminescence spectra of porous Si and attributed to the recombination via free excitons and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
(8 reference statements)
0
1
1
Order By: Relevance
“…The discrepancy is unclear at the moment. Chernoutsan et al observed PL emissions at 2.07 eV from porous InP (∼ 5 nm of the average size of InP nanostructures) formed in HCl [13]. Compared to their result, the PL blueshifted energy is smaller in our measurements.…”
contrasting
confidence: 88%
“…The discrepancy is unclear at the moment. Chernoutsan et al observed PL emissions at 2.07 eV from porous InP (∼ 5 nm of the average size of InP nanostructures) formed in HCl [13]. Compared to their result, the PL blueshifted energy is smaller in our measurements.…”
contrasting
confidence: 88%
“…The PL peak positions observed in our experiment is consistent with the reported results (Chernoutsan et al 2000;Schmuki et al 2000). Figures 3 and 4 and table 2 also show that peak positions (corresponding peak energies) in all porous samples are blue shifted from the bulk InP whose PL peak is at 1⋅34 eV (Levinshtein et al 1996).…”
Section: Photoluminescencementioning
confidence: 97%